Peranacang Sistem Informasi Penerimaan Sumbangan Pembinaan Pendidikan (SPP) pada SD Qur'an Al-Fityan Batusangkar - Putrasma, Rando Sony; Marlin, Khairul (UIN MAHMUD YUNUS BATUSANGKAR, 2021)
The problem was discussed in this study is the recording the receipt of the Educational Development Contribution (SPP) which still manually. The SPP acceptance report is not yet available computerized and there is no computerized recording system used to record SPP receipts at Al-Fityan Batusangkar Elementary School. The type of research that the author uses is the development using the SDLC (System Development Life Cycle) method, namely to create an accounting application program for SPP receipt transactions at Al-Fityan Batusangkar Elementary School by conducting a development model to produce. The applications used are PHP Native, Visual Studio Code, MySQL. The resulting product has implemented an accounting system application in recording the receipt of Educational Development Contributions (SPP) and has produced a receipt report and proof of payment. In addition, the product has also given good results against all elements of PIECES